AB0498 ASSOCIATION OF METABOLIC PATHWAY-RELATED SINGLE NUCLEOTIDE POLYMORPHISMS WITH ORAL METHOTREXATE TREATMENT OUTCOMES IN RHEUMATOID ARTHRITIS PATIENTS - Rahman, A. (Annals of the rheumatic diseases, 2024)
Background:Methotrexate (MTX) metabolic pathway-related single nucleotide polymorphisms (SNPs) are associated with its response, non-response, and developing adverse drug reactions (ADR), which may help in the modification of rheumatoid arthritis (RA) treatment.Objectives:To determine the association of metabolic pathway-related SNPs in the outcomes of oral MTX treatment in patients with RAMethods:This observational 12-week prospective study was conducted in the Department of Rheumatology, BSMMU, Dhaka, from November 2022 to August 2023. A total of 140 patients of RA were enrolled after having informed written consent. Four were dropped out. Every patient’s socio-demographic and clinical characteristics, disease activity (CDAI, DAS-28), functional status (B-HAQ), and quality of life (B-SF-36) were assessed at baseline and 12th week. CBC, CRP, SGPT, serum creatinine, rheumatoid factor (RF), and anti-CCP antibody (ACPA) were done. SNPs of the selected genes (RFC, FPGS, GGH, and MTHFR) were identified by polymerase chain reaction- Restriction Fragment Length Polymorphism (PCR-RFLP). All subjects were put on MTX 15mg weekly, which was escalated to 25 mg weekly if no ADR was observed. After 12 weeks, they were divided into responders and non-responders according to EULAR response criteria.Results:Analysis was done on 136 patients. The mean age at onset was 41.75±11.57 years, and the mean disease duration was 1.21±1.01 years. Among them, 103(75.7%) were women, and 93(68.6%) were from rural areas. Thirty-two (23.53%) were current tobacco users. Eighty-two (58.6%) had any form of extra-articular manifestations. Hypothyroidism 29(21.3%) and DM 21(15.4%) were common comorbidities. All subjects were seropositive (RF=86% or ACPA=95.6%). Of 136 subjects, 63 (46%) were responders, 38 (28%) were non-responders, and 35 (26%) developed ADR. Twelve patients (8.8%) discontinued MTX for severe adverse events. Among the studied SNPs, rs 3758149, a polymorphism of Gamma-glutamyl Hydrolase (GGH) was found to be associated with adverse events (p=0.009, OR= 4.09, 95% CI=1.5-11.1), and it was associated with nausea (p=0.006). The presence of any extra-articular manifestations (p=0.038) and baseline high B-HAQ (p=0.046) were predictors for nonresponse. Any comorbidity (p=0.017, OR=4.77,95% CI=1.32-17.30) and high baseline DAS28-ESR (p=0.010, OR=5.77,95% CI=0.71-47.23) were predictors for developing ADR.Conclusion:Studied SNPs were not associated with response and non-response of MTX. The SNP rs3758149 of GGH was related to an increased rate of ADR, specifically nausea. The presence of any extra-articular manifestations and baseline high B-HAQ were predictors for nonresponse. Any comorbidity and high baseline DAS28-ESR were predictors for developing ADR.REFERENCES:NIL.Acknowledgements:NIL.Disclosure of Interests:Atiqur Rahman Delta pharmaceuticals Ltd.